(untitled) (Daffodil International University Journal of Science and Technology, 2010)
To produce hydrophobic handmade paper internal material rosin along with external additive (MCC suspension), internal additive (wax emulsion) and reinforcement were used. Optimum result was obtained when rosin along with alum was used as internal additive during pulp preparation and MCC in the form of suspension was applied as external additive. The hydrophobicity was increased by 92.46% due to rosin-alum treatment and application of MCC suspension as external additive. It was also observed that application of wax along with rosin hampered/hindered the hydrophobicity. Keyword: Handmade, Jute, Paper, Hydrophobic, Sizing material DOI: 10.3329/diujst.v5i1.4381 Daffodil International University Journal of Science and Technology Vol.5(1) 2010 pp.48-52